KUALITAS PELAYANAN PUBLIK TRANSPORTASI FEEDER WIRA WIRI SUROBOYO DALAM PERSPEKTIF STANDAR PENYELENGGARAAN BIDANG LALU LINTAS DAN ANGKUTAN JALAN: KUALITAS PELAYANAN PUBLIK TRANSPORTASI FEEDER WIRA WIRI SUROBOYO DALAM PERSPEKTIF STANDAR PENYELENGGARAAN BIDANG LALU LINTAS DAN ANGKUTAN JALAN - Aulia, Aisyah; Arieffiani, Deasy (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Bhayangkara Surabaya, 2025)
This research examines the quality of public services for the Wira Wiri Suroboyo feeder transportation from the perspective of Road Traffic and Transportation Service Standards based on Government Regulation Number 30 of 2021. The purpose of this research is to analyze the quality of services provided to meet user expectations and their compliance with applicable public service standards. The analysis was conducted by integrating the five dimensions of service quality from Zeithaml et al.'s (1990) public service quality theory into the regulatory framework of Government Regulation No. The goal is to ensure that the 30th year of 2021 is safe, secure, efficient, effective, and balanced. The research findings indicate that the tangibles dimension (physical evidence) has supported safety and security aspects through the provision of standard facilities such as Closed Circuit Television (CCTV), accessibility, and priority seating. Operational systems and timeliness, along with competent vehicles and drivers, support the reliability dimension. The responsiveness dimension is evident in the speed and preparedness of friendly staff in handling passenger needs and complaints. Meanwhile, the dimensions of assurance and empathy do not fully reflect balanced service, especially in ensuring equal access and inclusive communication. This finding confirms the need for systemic improvements to ensure the quality of public services aligns with the basic transportation principles established by the government.